Determining heutagogy design elements for online learning model using Fuzzy Delphi methods - Hairi, Fairuzza; Mohamad, Siti Nurul Mahfuzah; Sahrudin, Saad; Ahmad, Ibrahim (Little Lion Scientific Islamabad Pakistan, 2023)
Teaching and learning in computer application courses are being improved by educators as technology continues to change the face of education. For the purpose to promote student participation and selfdirected learning, this study investigates how the heutagogical online learning paradigm might be adapted to computer application instructions. The Heutagogy Online Learning Model (HeuLEM) is a model that this research proposes based on heutagogy principles, including the six design elements of heutagogy. It enables learners to take control of their educational process, make knowledgeable choices, and develop critical skills for the digital age. Incorporating self-determined learning, reflection, strong interpersonal skills, and collaborative online tools, instructors can design an engaging and dynamic online learning environment that fosters students' digital collaboration abilities. HeuLeM comprises the theoretical underpinnings of heutagogy and offers helpful implementation tactics for the model in computer application courses. This study is to identify whether the six heutagogy design elements can be adapted to Heutagogy Online Learning Model to enhance the digital collaboration skills of students. A total of 12 experts were selected to analyze the fuzziness consensus of experts. All of the data obtained will be analyzed using the Fuzzy Delphi method. The findings show that all the heutagogy design elements are suitable to be adapted Heutagogy Online Learning Model to enhance the digital collaboration skills of students. The six heutagogy elements that explore, create, connect, share, reflect, and collaborate have reached unity with the threshold value of d ≤ 0.2 and the percentage of the expert group is more than 75%. Therefore, based on the consensus agreements, the development of Heutagogy Online Learning Model for enhancing the digital collaboration skills of students should be incorporated with the elements of heutagogy.